PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA BANK MEGA SYARIAH KOTA SINGKAWANG - B11108186, NUDIALIS SOLATA (Jurnal Manajemen Update, 2015)
Purpose in this research is to test and analyze the influence A Style Of Leadership AndMotivation Work  on the performance of employee at Bank Mega Syariah SingkawangCity.The research method used is descriptive and causal research which are associative withthe use of documentary studies, questionnaires, and interviews as a data collection technique.The population in this research is 34 employees, because population numbers less than 100then the authors use research with sampling population/ census, where all members of thepopulation serve as samples. The Data were analyzed using descriptive analysis and multiplelinear analysis to analyze the effect of the independent variable (X) to the dependent variable(Y).The results of this research concluded A Style Of Leadership has significant influence onthe performance of employees, because the value of siqnificant is greater than levelsiqnificant (0.970 > 0.05), and Motivation Hygiene Factor has significant influence on theperformance of employees because the value of siqnificant is smaller than the levelsiqnificant (0.002 ≤ 0.05). Keywords : A Style Of Leadership And Hygiene Factor Work, employee performance.